An Exploratory Study into Professional Scholarly Journals Publishing Software Adoption in Lithuania - Grigas, Vincas; Gudinavičius, Arūnas; Petreikis, Tomas; Šuminas, Andrius (Information & Media, 2023)
Introduction. This study investigates the adoption of professional scholarly journal publishing software in Lithuania, with a focus on the trends and patterns of its use in 2020. It underscores the limited research on proprietary software and the absence of comprehensive country-specific case studies.Method. We compiled a list of sources by manually reviewing all journal websites and independently verified the collected data against other databases. Additionally, we contacted publishers individually via email to clarify the data.Analysis. Data were analysed using descriptive analysis with the help of SPSS statistical package.Results. The analysis reveals that the second or third-generation Open Journal Systems (OJS) software is the most popular open-source publishing solution, utilized by nearly half of the Lithuanian journals. The Social sciences and Technology sciences are the most frequent users of OJS, both in Lithuania and abroad. The use of OJS in Lithuania gradually decreases to 24% as one moves from publication towards production management, with a significant reduction in the use of OJS for manuscript delivery. The increased use of proprietary software for manuscripts may be related to pricing and the composition of the journal's authors.Conclusions. The ecosystem of scholarly journals in Lithuania has not yet reached the minimum level of technological advancement where all journals use professional software for publishing.
Keywords: open-source; proprietary; Open Journal Systems; scholarly publishing; Lithuania